1998
DOI: 10.1002/(sici)1097-4636(19981215)42:4<634::aid-jbm21>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Microgrooved subcutaneous implants in the goat

Abstract: We investigated the behavior of microgrooved implants in soft tissue using polystyrene implantable disks, either smooth or microgrooved (1-10 microm) on both sides. The implants were placed subcutaneously in a goat for 1, 4, or 12 weeks. Light and transmission electron microscopy showed that fibrous capsule formation around the implants was fairly uniform. After 1 week the implants were covered with a fibrous capsule about 80 microm thick. The collagen matrix was loose, and many inflammatory cells were present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…The microgrooves in the silicone were directed either parallel to the long axis of the catheter (with grooves directed perpendicular to the skin) or circular around the catheter (parallel to the skin). Based on previous animal studies within our group, and the group of Brunette and coworkers, one of two types of texturing were applied: either 10‐μm‐wide and 1‐μm‐deep grooves,2–9 or 40‐μm‐wide V‐shaped grooves 10–13. The dimensions of the various implants are shown in Table I.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The microgrooves in the silicone were directed either parallel to the long axis of the catheter (with grooves directed perpendicular to the skin) or circular around the catheter (parallel to the skin). Based on previous animal studies within our group, and the group of Brunette and coworkers, one of two types of texturing were applied: either 10‐μm‐wide and 1‐μm‐deep grooves,2–9 or 40‐μm‐wide V‐shaped grooves 10–13. The dimensions of the various implants are shown in Table I.…”
Section: Methodsmentioning
confidence: 99%
“…Although microtexturing is known to have vast influence on the growth behavior of cells in vitro , current in vivo literature is scarce and does not demonstrate the applicability of microtexturing. For instance, a number of recent studies showed that microtexturing had no evident beneficial effects on the performance of soft‐tissue implants 5–9. In these studies, even an aggravated attraction of macrophages to textured surfaces was seen.…”
Section: Introductionmentioning
confidence: 99%
“…93 Stresses in this range (1-10 nN/cell contact) can cause remodeling of cell-cell contacts, cell extracellular matrix (ECM), and ECM. 42 Capsular contracture arising from constriction of the foreign body capsule has been reported to be strong enough to bend and fracture subcutaneously implanted polystyrene disks 94 and rupture breast implants. 95,96 Capsular contraction may not be relevant to available PerQ sensors but will become more relevant to sensor applications as the lifetime of fully implantable sensors is extended beyond 1-week implantation time.…”
Section: Contractile Forcesmentioning
confidence: 99%
“…This property of “contact guidance” is an important part of understanding the behavior of how pre-osteoblasts interact with the complex fibrin/platelet scaffold. There are a number of elegant in vitro and in vivo studies which document the importance of not just the roughness of an implant surface but the effect of the direction of the pattern (or epitaxis) [108111]. These studies demonstrate that fibroblasts and osteoblasts are capable of recognizing repeated surface features (e.g., lines, grooves and other defects created in machining).…”
Section: Implant Micro-retentive Features: Surface Roughness By Blastmentioning
confidence: 99%